Analyzing The Factors Influencing Students' Willingness To Communicate In Speaking Classes at Universitas Negeri Gorontalo - Herlina, Elin; Machmud, Karmila; Danial, Haris (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the psychological and situational factors that influence students' willingness to communicate (WTC) in speaking classes. This study focuses on second-year students of the English Education Study Program at Universitas Negeri Gorontalo who have completed the course “Speaking for Professional Context.” Using a qualitative design, data were collected through semi-structured interviews with ten participants selected through purposive sampling. Thematic analysis was used to identify the main themes in the data. The results of the study indicate that both psychological and situational factors significantly influence students' WTC. The most influential psychological factor is self-confidence, while the prominent situational factors include the interlocutor and the role of lecturers. Other prominent themes include learning anxiety, the influence of topic type on perceived communicative competence, classroom atmosphere, and instructor strategies. In practice, these findings can provide information and strategies for student learning and teaching activities in the classroom